The Role of Influencers in Restoring Brand Loyalty Among Previous Customers - Saleng, Sultan (Journal of Social Commerce, 2023)
In this research, the author explores the intended role of social media influencers in regaining consumer patronage of customers who have once used a particular product, and with a view of ascertaining the main influence of credibility, attractiveness, and relevance characteristics of the influencers. As the method of data collection, a quantitative method was used based on which 500 participants who have previously LOS’d a brand and who have been exposed to influencer driven marketing communication were chosen. The study further notes that credibility is the most influential determinant of brand loyalty restoration; secondly, relatability; thirdly, attractiveness. In addition, it was seen that micro influencers were more effective than macro-influencers in the context of consumer recall. These findings confirm the general approach to the choice of influencers and reveal the peculiarities of micro influencers for building credible relationships with the audience. This research fills the existing gap in the literature by diverging from the earlier work on factors influencing brand allegiance to a new perspective of re-allegiance to the brand, hence providing insights to both the scholars and the practitioners in the field of marketing.